2017
DOI: 10.1038/s41598-017-04033-9
|View full text |Cite
|
Sign up to set email alerts
|

Optofluidic device for the quantification of circulating tumor cells in breast cancer

Abstract: Metastatic cancer patients require a continuous monitoring during the sequential treatment cycles to carefully evaluate their disease evolution. Repetition of biopsies is very invasive and not always feasible. Herein, we design and demonstrate a 3D-flow focusing microfluidic device, where all optics are integrated into the chip, for the fluorescence quantification of CTCs in real samples. To test the chip performance, two cell membrane targets, the epithelial cell adhesion molecule, EpCAM, and the receptor tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…In the latter case, direct identification of tumor markers, such as cancer cells, contained in bodily fluids (i.e., liquid biopsies) likely represents the most powerful approach for the noninvasive and real-time monitoring of the disease progression or recurrence and the response to various treatments, which can also lead to key insights into the development of specific resistances (Schumacher and Scheper 2016;Siravegna et al 2017). In this regard, studies of integration of SEPs with modular microfluidic platforms have demonstrated the potential to efficiently combine in an assay the rapid sample processing and precise control of biofluids with the fast optical detection of cancer cells (Hoonejani et al 2015;Pedrol et al 2017;Sackmann et al 2014;Shields et al 2015;Zhou and Kim 2016).…”
Section: Sep Characterization Of Single Cellsmentioning
confidence: 99%
“…In the latter case, direct identification of tumor markers, such as cancer cells, contained in bodily fluids (i.e., liquid biopsies) likely represents the most powerful approach for the noninvasive and real-time monitoring of the disease progression or recurrence and the response to various treatments, which can also lead to key insights into the development of specific resistances (Schumacher and Scheper 2016;Siravegna et al 2017). In this regard, studies of integration of SEPs with modular microfluidic platforms have demonstrated the potential to efficiently combine in an assay the rapid sample processing and precise control of biofluids with the fast optical detection of cancer cells (Hoonejani et al 2015;Pedrol et al 2017;Sackmann et al 2014;Shields et al 2015;Zhou and Kim 2016).…”
Section: Sep Characterization Of Single Cellsmentioning
confidence: 99%
“…This requires larger equipment and staff specialized in electronics, however these inconveniences are currently being addressed. A microchip that integrates optics for fluorescence quantification of CTCs has been described and the results obtained using the optofluidic device were consistent with those obtained from flow-cytometry, conventional imaging and serological tests [124].…”
Section: Circulating Tumor Cellsmentioning
confidence: 68%
“…The application of antibodies against specific antigens toward particular cancers were also reported [115]. For example, anti-tyrosine-protein kinase receptor (anti-HER2) was employed for recognition of HER2 positive breast cancer [124]. An antibody for prostate-specific membrane antigen (PSMA) was used for prostate cancer circulating tumor cells entrapment [125].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…The most straightforward and widely investigated implementation of SERS to cancer-related applications is as an optical imaging technique for molecular characterization of tumor tissues in place of (or in combination with) fluorescence spectroscopy. SERS-encoded particles (SEPs) may substitute for fluorescent reporters [11,12,13] (typically, fluorescently-labelled antibodies selective for specific protein receptors on the cell surface) as contrast agents. SEPs always combine a SERS molecular code, yielding a unique vibrational fingerprint (signal read-out), bound to a plasmonic core (mostly, silver or gold), as required for the enhancement of the weak Raman signal (Figure 1A).…”
Section: Sers Imaging Of Cancer Tissues and Single Cellsmentioning
confidence: 99%